2015
DOI: 10.1002/bdrc.21114
|View full text |Cite
|
Sign up to set email alerts
|

Development of the infant intestinal microbiome: A bird's eye view of a complex process

Abstract: Infants undergo profound shifts in colonizing intestinal microorganisms during their first year, especially during and after birth and during weaning. Microbiota are passed to infants through the placenta, during the vaginal birth process, and from early diet and other environmental exposures. These microbiota play an active role in the development of healthy infant metabolic and immunologic systems; profound shifts in microbiotal populations can be persistent, are associated with immediate alterations in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 110 publications
0
25
1
Order By: Relevance
“…Although almost sterile before birth, infants’ nasopharyngeal and gastrointestinal tracts become progressively colonized with a diverse, complex, and interacting array of microorganisms [14]. This creates an opportunity to study colonization and resistance starting from a microbiological “tabula rasa.” The objective of this study was to characterize the longitudinal colonization with bacterial pathogens and associated antibiotic resistance in a cohort of community-dwelling infants in Northeast Ohio, to describe antibiotic and daycare exposures, and to pilot procedures for a larger cohort study powered for hypothesis testing.…”
mentioning
confidence: 99%
“…Although almost sterile before birth, infants’ nasopharyngeal and gastrointestinal tracts become progressively colonized with a diverse, complex, and interacting array of microorganisms [14]. This creates an opportunity to study colonization and resistance starting from a microbiological “tabula rasa.” The objective of this study was to characterize the longitudinal colonization with bacterial pathogens and associated antibiotic resistance in a cohort of community-dwelling infants in Northeast Ohio, to describe antibiotic and daycare exposures, and to pilot procedures for a larger cohort study powered for hypothesis testing.…”
mentioning
confidence: 99%
“…In spite of this, it is currently well demonstrated that the delivery mode is one of the main drivers on the colonization and correct establishment of the gut microbiota. Several studies have confirmed different intestinal microbiota patterns between CS and VD babies; however, the source of microbial transmission is not wholly clear [9]. CS babies are not directly exposed to mother vaginal microbiota, so this first inoculum comes from other maternal localizations, such as skin or mouth, or from non-maternal sources like the surrounding delivery environment [10].…”
Section: Development Of Microbiome In Cs Babiesmentioning
confidence: 98%
“…Weaning is another important stage, where the gut microbiota becomes more complex and diverse [9]. The timing and selection of the first solid foods are factors that have an important effect in the correct development of the gut microbiota.…”
Section: Perspectives and Future Trends On The Research About The Relmentioning
confidence: 99%
“…The most dramatic changes in composition occur in infancy and early childhood 5. The intestinal microbiome of an infant is affected by gestational age (full term or premature), mode of delivery (vaginal birth or caesarean section), type of feed (breast milk or formula feeds), maternal nutritional status (overweight or undernourished) and use of antibiotics 6. The complexity and plasticity of the infant microbiota during this early-life development is believed to be important in maintaining homeostasis with the host's immune system and has an impact on health later in life 7…”
Section: Microbiome Compositionmentioning
confidence: 99%